Assessing Variances in Dentist’s Interpretations of Antibiotic Prophylaxis Guidelines: A Survey of Dental School Faculty - Jennifer Bereckis; Susan Rowan; Danny Hanna; Aniruddh Narvekar; Anne Koerber (International Journal of Dentistry)
Conclusions: Data gathered revealed a difference of opinions among dental faculty concerning the appropriate dental procedures warranting the prescription of AP for patients at risk of IE. Similarly, there was a lack of consensus among dental faculty regarding dental procedures specifically involving GM. The discordance observed between these two categories implies a potential lack of clarity in the 2007 AHA guidelines. The criteria related to GM for determining the necessity of AP in high-risk individuals may introduce confusion for dental faculty, possibly extending to dentists practicing in nonacademic settings. Such ambiguity can potentially contribute to inappropriate decision-making regarding the prescription of AP.